Orthopedic complications after osteotomy in patients with classic bladder exstrophy and cloacal exstrophy: a comparative study. Issue 5 (October 2022) - Sholklapper, Tamir N.; Crigger, Chad; Haney, Nora; Khandge, Preeya; Wu, Wayland; Sponseller, Paul D.; Gearhart, John P.
Summary: Background: The addition of pelvic osteotomy to the armamentarium of tools for correction of classic bladder exstrophy (CBE) and cloacal exstrophy (CE) has undeniably served as one of the most effective advancements in improving the likelihood of successful primary bladder closure. Osteotomy-related complications have been studied and documented extensively in patients with CBE, yet evaluation remains limited in CE concordant with its relative rarity. Objective: To compare orthopedic complications in patients with CBE and CE who underwent primary bladder closure with osteotomy. Methods: A prospectively maintained, IRB-approved database of 1401 exstrophy-epispadias patients was reviewed for patients with CBE or CE after primary closure and pelvic osteotomy performed at a single institution from 1975 to 2021. Failed closure was defined as dehiscence, bladder prolapse, or vesicocutaneous fistula at any point. Surgery or anesthesia-related complications were captured within 6 weeks of osteotomy or closure. Results: A total of 146 patients were included in the analysis with 109 and 37 patients with CBE and CE, respectively. Between the CBE and CE cohorts, there were significant differences in median age at primary closure (68 days [IQR 10–260] vs 597 [448–734]; p < 0.001), diastasis width (4 cm IQR [3.8–4.6] vs 6.1 [5.0–7.2]; p < 0.001), osteotomy at time of closure (99.1% vs 75.7%; p < 0.001), and utilization of external hip fixation (67.9% vs 89.2%; p = 0.011). There was no significant difference by gender, osteotomy technique, or hip immobilization technique. Regarding exstrophy closure outcomes, there were 5 failures in the CBE group and 1 in the CE group (p = 1.000). Complications were experienced in 38.5% and 56.8% of CBE and CE patients (p = 0.054) with a significant difference in orthopedic complications (primarily consisting of superficial pin-site infections) between the cohorts (4.6% vs 16.2%, p = 0.031). There was no significant difference in grade 3 or higher complications between cohorts (5.5% vs 13.5%, p = 0.147). Discussion: This was the first study comparing orthopedic complications after osteotomy between CBE and CE, providing valuable insight into which factors vary among cohorts and which are associated with increased complication rates. Despite availability of high case numbers for these rare disorders, the analysis continued to be limited sample size and missing data for retrospective analysis. Conclusions: While exstrophy closure success and overall complications rates are similar in patients with CBE and CE, patients with CE experience more superficial pin-site infections after pelvic osteotomy. External hip fixation may be associated with the increase in orthopedic complications, though further research is required to elucidate the underlying cause of these complications.